The Effect Of Training And Work Environment on Employee Performance on Badan Pendapatan Daerah Kota Tasikmalaya - Rahmi Radhiah Ramadhani; Arga Sutrisna; Kusuma Agdhi Rahwana (Penerbit Jurnal Indonesia, 2023)
This research was conducted with the aim of knowing the effect of training and the work environment on employee performance at the Tasikmalaya City Regional Revenue Agency. This research uses a quantitative approach using the method in this study is the associative method (causality) using data obtained directly through questionnaires distributed to 50 respondents who are employees and have attended training. The technique used in this study is multiple linear regression. The research results show that: (1) Training and work environment simultaneously have a significant effect on employee performance; (2) Partial training has no significant effect on employee performance; (3) Work environment partially has a significant effect on employee performance